Relative Abundance of Megabenthic Organisms in the Seagrass Ecosystem of Mantang Island, Riau Islands Province, Indonesia - Nugraha Aditya Hikmat; Ma’mun Asep; Febrianto Try; Januarni Wisa; Aiin Noor (BIO Web of Conferences)
Seagrass ecosystems play a crucial role in coastal environments, providing essential habitats for the survival of various marine species. One significant group associated with these ecosystems is benthic organisms, which inhabit the ocean floor. This study aims to evaluate the relative abundance of megabenthic organisms in the seagrass ecosystem surrounding Mantang Island. Sampling was conducted at three stations. The results showed that seagrass cover in the waters of Mantang Island ranged from 25.5% to 40.31%, indicating a moderate level of seagrass coverage. Four main groups of megabenthic organisms were identified: Astropecten sp., Atrina pectinata, Strombus sp., and Trachycardium sp., with Strombus sp. exhibiting the highest relative abundance. These findings provide insight into the ecological health of the seagrass ecosystem in the region.